Pengaruh Proses Pemasakan Singkong terhadap Profil Senyawa Linamarin (β-Gluksosida Sianogenik) - Mohammad Mardiyanto; Achmad Subagio; Nurul Isnaini Fitriyana (Politeknik Negeri Jember, 2023)
Cassava is one of the third staple foods after rice and corn. However, cassava contains cyanogenic β-glucoside compounds in the form of linamarin compounds which have the potential to be hydrolyzed into HCN compounds (cyanide acid). In addition, cassava is included in foodstuffs that cannot be consumed directly, so it needs to be cooked. Therefore the purpose of this study was to determine the effect of the cooking process (boiling, steaming, and frying) on ​​the linamarin compound profile. The results of testing the linamarin profile using FTIR obtained linamarin vibrates at a wavelength of 4000-500 cm-1 with transmittance of 70-100%.